Vertical Greenery as Natural Tool for Improving Energy Efficiency of Buildings - Carlo Alberto Campiotti; Lorenzo Gatti; Alessandro Campiotti; Luciano Consorti; Patrizia De Rossi; Carlo Bibbiani; Rosario Muleo; Arianna Latini (Horticulturae, 2022)
The European Construction Sector Observatory outlined that green building envelopes as green roofs and walls contribute to the reduction of energy demand and CO2 emissions due to the air conditioning in summer periods, and the mitigation of heat islands in urban areas. For this reason, the understanding about the contribution of urban greening infrastructures on buildings to sustainable energy use for air conditioning is urgent. This paper focuses on the analysis of a vertical surface provided with a Parthenocissus quinquefolia (L.) Planch., a winter deciduous species, as green cover of a building, assessing the reduction of the solar radiation energy absorbed by the façade and, consequently, the heat flux (HF) transmitted into the internal ambient. This research shows that, in July, surface temperatures (STs) on the vegetated façade were up to 13 °C lower than on the unvegetated (bare) façade. Under the climate and environmental conditions of the green wall located at ENEA Casaccia Research Center, a saving of 2.22 and 1.94 kWhe/m2, respectively in 2019 and 2020, for the summer cooling electricity load, was achieved. These energy reductions also allowed the saving of 985 and 862 g CO2/m2 emissions, respectively, in 2019 and 2020. Ultimately, a green factor named <semantics><msubsup>Kv*</msubsup></semantics> was also elaborated to evaluate the influence of vegetation on the STs as well as on HFs transmitted into the indoor ambient and adapted to the case of a detached vertical green cover. Measurements of <semantics><msubsup>Kv*</msubsup></semantics> factor lasting three years showed the suitability of this index for defining the shading capacity of the vegetation on the building façade surfaces, which can be used to predict thermal gains and effects in a building endowed of a vertical green system.